Quality evaluation of selected vegetables under rain shelter and open field cultivation - Nashath K H (Department of Home Science, College of Horticulture, 2005)
The study on “Quality evaluation of selected vegetables under rain shelter and open field cultivation” was aimed at assessing the duration of maturity, nutritional composition, anti nutritional factors and acceptability of the two varieties of amaranth, capsicum and tomato cultivated under rain shelter and open field in rainy season in the Department of Olericulture, College of Horticulture, Vellanikkara.